ANO1: central role and clinical significance in non-neoplastic and neoplastic diseases - Hu, Yanghao; Zhang, Yifei; He, Jiali; Rao, Huihuang; Zhang, Duomi; Shen, Zhisen; Zhou, Chongchang (Frontiers in Immunology, 2025)
Anoctamin 1 (ANO1), also known as TMEM16A, is a multifunctional protein that serves as a calcium-activated chloride channel (CaCC). It is ubiquitously expressed across various tissues, including epithelial cells, smooth muscle cells, and neurons, where it is integral to physiological processes such as epithelial secretion, smooth muscle contraction, neural conduction, and cell proliferation and migration. Dysregulation of ANO1 has been linked to the pathogenesis of numerous diseases. Extensive research has established its involvement in non-neoplastic conditions such as asthma, hypertension, and gastrointestinal (GI) dysfunction. Moreover, ANO1 has garnered significant attention for its role in the development and progression of cancers, including head and neck cancer, breast cancer, and lung cancer, where its overexpression correlates with increased tumor growth, metastasis, and poor prognosis. Additionally, ANO1 regulates multiple signaling pathways, including the epidermal growth factor receptor (EGFR) pathway, the mitogen-activated protein kinase (MAPK)/extracellular signal-regulated kinase (ERK) pathway, and phosphatidylinositol 3-kinase (PI3K)/protein kinase B (AKT) pathway, among others. These pathways are pivotal in regulating cell proliferation, migration, and invasion. Given its central role in these processes, ANO1 has emerged as a promising diagnostic biomarker and therapeutic target. Recent advancements in ANO1 research have highlighted its potential in disease diagnosis and treatment. Strategies targeting ANO1, such as small molecule modulators or gene-silencing techniques, have shown preclinical promise in both non-neoplastic and neoplastic diseases. This review explores the latest findings in ANO1 research, focusing on its mechanistic involvement in disease progression, its regulation, and its therapeutic potential. Modulating ANO1 activity may offer novel therapeutic strategies for effectively treating ANO1-associated diseases.